Unraveling key interactions and the mechanism of demethylation during hAGT-mediated DNA repair via simulations - T. G., Shruti; Siddiqui, Shakir Ali; Dubey, Kshatresh Dutta (Frontiers in Molecular Biosciences, 2022)
Alkylating agents possess the biggest threat to the genomic integrity of cell by damaging DNA bases through regular alkylation. Such damages are repaired by several automated machinery inside cell. O6-alkylguanine-DNA alkyltransferase (AGT) is such an enzyme which performs the direct repair of an alkylated guanine base by transferring the alkyl group to a Cysteine residue. In the present study using extensive MD simulations and hybrid QM/MM calculations, we have investigated the key interactions between the DNA lesion and the hAGT enzyme and elucidated the mechanisms of the demethylation of the guanine base. Our simulation shows that the DNA lesion is electrostatically stabilized by the enzyme and the Arg135 of hAGT enzyme provides the main driving force to flip the damaged base into the enzyme. The QM/MM calculations show demethylation of damaged base as a three step in thermodynamically feasible and irreversible manner. Our calculations show that the final products forms via Tyr114 in a facile way in contrast to the previously proposed Lys-mediated route.